CONTROVERSIAL BEHAVIOR OF POLITICAL ELITES IN INDONESIA DURING THE COVID-19 - Anang Sujoko; Khusnul Khatimah; Amalia Dewi Masyitah; Dicky Wahyudi (al-Balagh : Jurnal Dakwah dan Komunikasi, 2022)
The Covid-19 pandemic, which has accounted for remarkable casualties in Indonesia, did not seem to make political elites more empathetic. The study aims to reveal how the mythology of the political elites behind the criticism of Instagram accounts @GejayanMemanggil.  To fulfill this goal, we employed Roland Barthes' semiotic analysis of nine contents of @GejayanMemanggil. This study has revealed five major results. First, the mythology of the political elite is represented as the 'ancilus' of oligarchic interests during the Covid-19 pandemic. Second, political elites and oligarchs have superior positions to control society and health workers. Third, the political elites' policies focus more on economic recovery than the people’s safety. Fourth, @GejayanMemanggil Instagram account narrates the mythology of political elites who have no sensitivity towards people’s hardship because they exploit their positions and facilities as public officials. Finally, political elites show that they do not empathize with the suffering of the people during the Covid-19 pandemic.